Menalar Demokrasi dalam Masyarakat Sipil: Teori dan Gagasan Baru dalam Pemikiran Gideon Baker - Erisanna, Amelia; Akbar, Merly Septia Afsani (Jurnal PKM Manajemen Bisnis, 2025)
Civil society plays an important role in the development and consolidation of democracy, especially in creating space for political participation, policy advocacy, and oversight of the government. In this context, Gideon Baker's Theorising the Democracy of Civil Society offers a new perspective on the role of civil society in shaping democracy independent of state domination. Baker proposes that democratisation is not only dependent on the state, but can also develop through self-organisation in civil society. This view criticises traditional theories of democracy that focus too much on the state as the main actor in the democratisation process. The theoretical study in this research refers to Baker's thoughts on democracy that is rooted in civil society and not tied to state structures. Other literature also suggests that although civil society plays an important role in democracy, it often faces external and internal challenges, including autocratisation and restrictions on civil liberties. The purpose of this research is to analyse more deeply Baker's ideas and examine their relevance in the context of contemporary democracy, especially in developing or authoritarian countries. The research method used is qualitative research with a book review approach, in which the researcher reads and analyses the book critically to explore the ideas and arguments put forward by the author, and compares them with existing literature. The results show that although Baker's concept of democracy in civil society still needs further development, it provides room for new thinking about a more inclusive and independent form of democracy. Suggestions for future research include exploring the application of this concept in social movements in developing or authoritarian countries and exploring how digital technology can strengthen civil society-based democracy.